2014
DOI: 10.1038/eye.2013.294
|View full text |Cite
|
Sign up to set email alerts
|

Portsmouth visual field database: an audit of glaucoma progression

Abstract: Aim To explore visual field (VF) progression in a cohort of secondary care-treated glaucoma and ocular hypertensive (OHT) patients. Methods We extracted VFs from our database drawn from our normal clinical practice. VF series from 4177 eyes from 2208 patients who had five or more VFs were obtained, the 'better' eye was selected and the rate of VF progression was calculated using mean deviation (MD) data. Results The median rate of progression for the whole sample was À 0.1 dB/year (interquartile range (IQR) À … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 34 publications
1
31
1
Order By: Relevance
“…Some definitions of fast progression have been fairly arbitrary with round numbers such as a VF MD rate of -1.5 dB/year [30, 33]or -2 dB/year [18, 40], commonly chosen. Without doubt, these rates would almost always have a deleterious impact on a patient’s visual health.…”
Section: Rates Of Visual Field Lossmentioning
confidence: 99%
“…Some definitions of fast progression have been fairly arbitrary with round numbers such as a VF MD rate of -1.5 dB/year [30, 33]or -2 dB/year [18, 40], commonly chosen. Without doubt, these rates would almost always have a deleterious impact on a patient’s visual health.…”
Section: Rates Of Visual Field Lossmentioning
confidence: 99%
“…In total, 23.9% of eyes in our study were non-progressors compared with 65.9% in Kirwan et al cohort (Table 3). 1 We also had proportionally more fast progressors than Chauhan et al, who in a study of 2324 eyes reported only 1.5% of eyes as having a progression rate of faster than 2 dB/year, eyes they labelled as catastrophic progressors. 4 Similarly, Saunders et al found only 3% of glaucomatous eyes lost 41.5 dB/year.…”
Section: Discussionmentioning
confidence: 95%
“…Figure 2b shows fitted slopes of change in MD for all eyes. According to the criteria defined by Kirwan et al, 1 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations